2020
DOI: 10.1108/rbf-04-2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of heterogeneity in investors' opinions on IPO valuation: evidence from the Pakistan stock market

Abstract: PurposeThis study investigated the effect of pricing mechanism and oversubscription on the heterogeneity of investors' opinions on initial public offering (IPO) valuation.Design/methodology/approachBesides the ordinary least square method, this study incorporated robust least square, stepwise least square and quantile regression methods to investigate the aftermarket behaviour of investors using the price range on the first day of trading of 82 IPOs listed on the Pakistan stock exchange.FindingsThe aftermarket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…A weak legal system can be strengthened to protect the interests of existing investors, potential shareholders and managers (Porta et al, 1998). Finally, risk is measured as a reciprocal of the offer price (Mehmood, et al, 2020c). The risk of an IPO can be inferred from its final offer price; firms with higher risk offer lower prices to attract investors, resulting in higher demand and higher IPO underpricing.…”
Section: Empirical Modelmentioning
confidence: 99%
“…A weak legal system can be strengthened to protect the interests of existing investors, potential shareholders and managers (Porta et al, 1998). Finally, risk is measured as a reciprocal of the offer price (Mehmood, et al, 2020c). The risk of an IPO can be inferred from its final offer price; firms with higher risk offer lower prices to attract investors, resulting in higher demand and higher IPO underpricing.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Doing so benefit issuers by reducing opinion heterogeneity among investors, which leads to lower underpricing. A negative correlation is also documented between book building (Mehmood et al, 2020) and institutional ownership (D. Sundarasen, 2019;Darmadi and Gunawan, 2013;Dumrongwong, 2020). This highlights the essential role institution's retention strategy plays in reducing information asymmetry as well as maintaining market stability.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 79%
“…Other determinants are associated with mixed results depending on the study's country. For instance, there is a negative correlation with oversubscription in Pakistan (Mehmood et al, 2020), yet a positive one in Greece (Kenourgios et al, 2007). Mixed results are reported by other studies (Dhamija and Arora, 2017;Hearn, 2014;Javid and Malik, 2016;Omran, 2005;Sahoo and Rajib, 2010;Tran et al, 2013).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 82%
“…Other studies, including Loughran and Ritter (2002) and Ljungqvist and Wilhelm (2005) support the information cascades model. Mehmood et al (2020) also found that the pricing mechanism and the premium offered in IPOs have significant bearing on the initial return.…”
Section: Extant Literaturementioning
confidence: 94%
“…They also argued that high-profile investment banks have more considerable skills and networks to ensure more access to the market. Mehmood et al (2020) and Mehmood et al (2021) studied the Pakistan IPO market and document that the postIPO behavior of the investors and initial return of IPO are influenced by pricing structure of the IPO, extent of oversubscription, degree of leverage and political stability. Signaling hypothesis and information cascades: The signaling model for IPO UP is suggested by Welch (1989), Grinblatt and Hwang (1989) and Allen and Faulhabar (1989). These studies suggest that quality issues segregate themselves from other IPOs by incurring a cost, i.e.…”
Section: Extant Literaturementioning
confidence: 99%